Four Legs Good, Two Legs Bad? Animal Welfare vs the World Trade Organisation (Featuring Article XX of the General Agreement on Tariffs and Trade and Article 2 of the Technical Barriers to Trade - Cunningham, Robert; Vindedzis, S. (Adelaide Law Review Association, 2017)
This article explores whether animal welfare can be deployed as a legitimate restriction on trade under the World Trade Organization framework. Article XX of the General Agreement on Tariffs and Trade and Article 2 of the Technical Barriers to Trade are traversed; along with the two relatively recent cases of US — Tuna II (DS381) and EC — Seal Products (DS400/401). While the World Trade Organization has traditionally demonstrated a reluctance to legitimise animal welfare based restrictions, contemporary World Trade Organization case law signals the possibility of a shifting landscape. The article argues that further development of coherent principles is required for the benefit of both animal welfare and trade certainty. This is particularly so in relation to the interrelated issues of extraterritoriality and coercion.